Ketersediaan Lahan Pertanian Padi Sawah Pasca Tsunami di Kabupaten Aceh Besar - Elvira Iskandar (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. Tsunami Aceh was the most terrific disaster in 40 years. The estimation of total losses were US 210 million, concentrated in two main sectors: infrastructure and housing and the productive sector. Agriculture showed the largest share of damage in productive sector, needs more attention to be rehabilitated in order to stimulate economic activity. This research aim to evaluate the progress of agricultural land rehabilitation in providing land to be cultivated by the farmer. Research conducted in Aceh Besar District by using survey methods. Research results showed that 77% of total farmland damaged due to tsunami, but the availability of lowland paddy field after tsunami only reached 16,7% from total farmland before tsunami. There were no significant difference between the rehabilitation processes conducted in low and high level of damaged based on Mann Whitney test. There was a lack of access to the farmland due to a limitation in farmland rehabilitation. This condition will lead to the difficulties of the community to back to their previous activity as a farmer since the majority occupation of affected communities were in agriculture field.